2019
DOI: 10.1111/prd.12291
|View full text |Cite
|
Sign up to set email alerts
|

Effects of occlusal forces on the peri‐implant‐bone interface stability

Abstract: The Glossary of Prosthodontic Terms defines occlusion as the 'act or process of closure, being closed or shut off and the static relationship between the incising or masticating surfaces of the maxillary or mandibular teeth or tooth analogs'. 1 To achieve the dental occlusion, the skeletal and muscular systems work simultaneously to produce the mandibular movement, which transfers force to the prosthesis, teeth, implants, and adjacent supporting bone. 2 But the dental/implant occlusion is not just a simple con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 153 publications
1
35
1
2
Order By: Relevance
“…Therefore, the internal screw might play an important role in the progression of bone loss in the presence of peri‐implantitis. This is probably due to the fact that when implants are in function, occlusal forces are dissipated through the occlusal surfaces, prosthetic structure, implant‐abutment connection, internal screw, implant body, implant‐to‐bone interface, and surrounding bone 38,39 . In fact, when transverse occlusal forces are applied on an implant, bending of the implant components occurs and only a reduced portion of the supporting bone is involved in counteracting the load; leading to higher stress levels in particular portions of the implant‐bone interface 53 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the internal screw might play an important role in the progression of bone loss in the presence of peri‐implantitis. This is probably due to the fact that when implants are in function, occlusal forces are dissipated through the occlusal surfaces, prosthetic structure, implant‐abutment connection, internal screw, implant body, implant‐to‐bone interface, and surrounding bone 38,39 . In fact, when transverse occlusal forces are applied on an implant, bending of the implant components occurs and only a reduced portion of the supporting bone is involved in counteracting the load; leading to higher stress levels in particular portions of the implant‐bone interface 53 .…”
Section: Discussionmentioning
confidence: 99%
“…found that implants with restoration emergence angle ≥30° had significantly more marginal bone loss compared with implants with restoration emergence angle <30°, 5 years following functional loading 24 . When implants are in function, occlusal forces propagate from the occlusal surfaces to the implant‐abutment connection and further to the internal screw of the implant 38,39 . If occlusal overload occurs, the internal screw may be prone to fracture or loosening 40–42 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even we can draw a conclusion that the success of implants in clinical work is inseparable from the development of materials science. In addition to material science, the survival rate of implant is influenced by other factors including occlusal forces [61]. The correlation between them is also reflected in this study.…”
Section: Biomed Research Internationalmentioning
confidence: 54%
“…Although a relationship between bone loss and overloading has not yet been established, and experimental and clinical data are contradictory, the stimulatory/deleterious effects of mastication forces cannot be excluded as a potential factor that, in conjunction with plaque and inflammation, might result in crestal bone loss. The transmission of force from the restoration to the peri‐implant bone, and the mechanotransduction phenomena responsible for cell and tissue responses, have been addressed by Delgado‐Ruiz et al in this volume of Periodontology 2000 .…”
Section: Overloading—biomechanical Considerationsmentioning
confidence: 99%